REVALUASI AKTIVITAS DI PENDIDIKAN TINGGI SETELAH PANDEMI COVID-19 UNTUK NEGARA BERKEMBANG - Noir Primadona Purba; Ibnu Faizal (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
The higher education academic system has been affected due to COVID-19 Pandemic. Nowadays, the adjustment in curriculum and research adapt to the pandemic and be used in the future. The research aims to give an evaluation in education and research system in higher education during the pandemic. Moreover, this approach can give the direction for changes and adaptations for this era. The research method uses article reviews in several reputable journal websites, reports, and government regulation continued with comparative analysis. The result is the higher education has affected severely during the pandemic. Tridharma activities need to be evaluated to accommodate the best solving problem for this problem. Almost all Universities in Indonesia has changed their learning system to online and limited research conducted. Furthermore, the biggest challenge lies in internet connection and technology knowledge. In the end, complete evaluation becomes an obligation to fulfil the new learning system before being implemented after the pandemic. Technology investment and quality assurance also need to consider to decide the best learning method for the future.